The capacity of major countries in Southeast Asia in meeting biodiesel mandates and pursue higher blends based on available major feedstocks. Issue 5 (28th May 2022) - Go, Alchris Woo; Agapay, Ramelito C.; Ju, Yi-Hsu; Conag, Angelique T.; Toledo, Arjay S.; Angkawijaya, Artik Elisa; Tran Nguyen, Phuong Lan
Abstract: Major economies in Southeast Asia have been pressing the use of renewable diesel (RD) as an alternative to petroleum diesel. Currently, the major RD produced and consumed in Southeast Asia is biodiesel (BD), produced from edible oils. The use of edible oils produced by Southeast Asian countries is also consumed in various industries. This gives rise to the need to have a quantitative long-term assessment of their potential availability for BD production. In this study, the potential existing major raw material that could be tapped for biodiesel production in Southeast Asia was identified. Future demands for biodiesel and the amount of biodiesel that could potentially be produced were also estimated. These are to provide a practical assessment of the readiness of the Southeast Asian countries in the use of BD. Only Indonesia and Malaysia have surplus oils from oilseeds for BD production. However, if the trade of resources is limited within major countries in Southeast Asia, the blending of BD could be increased up to 50 to 70% in diesel fuels until the year 2040. The minimum biodiesel production potential in Southeast Asia is 36 Mm 3 per year to as much as ∼61 to 87 Mm 3 by 2040.